Diamorphine infusion in the preterm neonate. Issue 10 (October 1991) - Elias-Jones, A C; Barrett, D A; Rutter, N; Shaw, P N; Davis, S S
Abstract : The effects of diamorphine were studied in 34 premature neonates who were given a loading dose of 50 micrograms/kg of diamorphine followed by a constant rate intravenous infusion of 15 micrograms/kg/hour. Small but significant falls were noted in blood pressure (at 30 minutes) and heart rate (at 30 minutes, six hours, and 12 hours) after administration of diamorphine, but these did not appear to cause any clinical deterioration and were thought to be related to the sedative effect of the drug. A significant fall in respiration rate at 30 and 60 minutes reflected the desired intention to encourage synchronisation of the infants' breathing with the ventilator. The mean (SD) plasma concentration of morphine measured during the infusion at steady state was 62.5 (22.8) ng/ml (range 20 to 98 ng/ml). The data suggest that this dosage regimen of diamorphine is safe. It results in plasma concentrations of morphine in the premature neonate which are comparable with those that are known to provide effective analgesia in the child and adult.